Investigating the potential of the slurry technology for sustainable pig farm heating. (1st November 2021) - Blázquez, Cristina Sáez; Borge-Diez, David; Nieto, Ignacio Martín; Maté-González, Miguel Ángel; Martín, Arturo Farfán; González-Aguilera, Diego
Abstract: Sustainable energy development in the farming sector is an essential strategy to respond the combined challenge of achieving a reliable and affordable solution but including mitigation and adaptation to climate change. Intensive breeding farms require maintaining an adequate indoor thermal environment that results in high energy demands, usually covered by fossil fuels and electricity. This paper addresses the application of the combined slurry technology for a particular pig farm that currently uses a diesel boiler to supply the piglet heating energy needs. The study also considers different options based on closed ground source heat pump systems. After the design of the slurry alternative and the geothermal ones, notable advantages are detected compared to the existing diesel system. Results show that the implementation of the slurry technology implies an important reduction of the operational costs, which, in turn, involves short amortization periods for this system in relation to the diesel one. Greenhouse gases emissions are also highly reduced in the slurry alternative based on the low electricity use of the heat pump. The environmental side is reinforced by the reduction of polluting substances such as methane of ammonia derived from the descent of temperature of the slurry. Graphical abstract: Image 1 Highlights: Slurry technology has been evaluated and designed for covering the heating needs of a pig farm under study. Slurry alternative has been compared to the existing diesel boiler and the conventional ground source heat pump systems. GES-CAL software has allowed the design of the remaining geothermal installations. Results show clear advantages for the slurry technology both from the economic and the environmental points of view.